(untitled) (Pakistan Journal of Science, 2022)
The advancement in technologies has provoked the trend of multimedia data exchange with smart devices. The smart devices have variant characteristics like low processing power, small computational capabilities and memory capacity etc. Therefore, there was a need to transmit video with maximum compression and security by minimal utilization of processing power and network bandwidth. Two widely used encoders for the video compression i.e. Advanced Video Coding (H.264/AVC) and Highly Efficient Video Coding (HEVC) were used for device selection. H.264/AVC was energy efficient but provided less compression rate than HEVC. However, due to differing capabilities of smart devices in terms of energy and storage, there was a need to devise a mechanism to automatically detect a video encoder as per device requirements. This paper has proposed two novel schemes: firstly, a Fuzzy Rules Based (FRB) system to auto detects encoder by taking the smart devices with their genuine capabilities like energy, storage and bandwidth etc. at destination and secondly, a lightweight Selective Encryption (SE) scheme to secure the output video produced by each encoder. This FRB implementation system proved to be a pioneer work in this field of exchanging secure compressed multimedia for smart devices and provided average 95% accuracy in choosing correct encoder with security.